‘Under the magnolia tree, our youth’: an autoethnography on friendship and sisterhood among female international doctoral students in New Zealand - Anh Ngoc Quynh Phan (Kōtuitui, 2025)
This paper demonstrates how my friendship with three other female Vietnamese doctoral students in New Zealand grew into an ‘academic sisterhood’ which was forged as an emplaced form of sociality that encouraged solidarity among us. As four female Vietnamese PhD students in New Zealand who shared intersecting identities as Vietnamese temporary migrants, women, mothers, and PhD students, we provided support for and learned from each other. The sisterhood strengthened my sense of belonging to both my home and host countries, and created a learning space for myself. I argue that the academic sisterhood was far more complexly imagined and meaningful than simple bonding networks of co-ethnic friendships, embracing the mixed emplaced and transnational nature of my friendship.